Theoretical investigation of metal magnetic memory testing technique for detection of magnetic flux leakage signals from buried defect. Issue 1 (2nd January 2018) - Xu, Kunshan; Qiu, Xingqi; Tian, Xiaoshuai
Abstract: The metal magnetic memory testing (MMMT) technique has been extensively applied in various fields because of its unique advantages of easy operation, low cost and high efficiency. However, very limited theoretical research has been conducted on application of MMMT to buried defects. To promote study in this area, the equivalent magnetic charge method is employed to establish a self-magnetic flux leakage (SMFL) model of a buried defect. Theoretical results based on the established model successfully capture basic characteristics of the SMFL signals of buried defects, as confirmed via experiment. In particular, the newly developed model can calculate the buried depth of a defect based on the SMFL signals obtained via testing. The results show that the new model can successfully assess the characteristics of buried defects, which is valuable in the application of MMMT in non-destructive testing.